Septicaemia of subterranean termites Coptotermes curvignathus caused by disturbance of bacteria isolated from termite gut and its foraging pathways. Issue 8 (26th August 2020) - Chin, Kit Ling; H'ng, Paik San; Wong, Wan Zhen; Lee, Chuan Li; Khoo, Pui San; Luqman, Abdullah Chuah; Ashaari, Zaidon; Gandaseca, Seca
Abstract : Microbial pathogens continue to attract a great deal of attention to manage the termite population. Every bacterium has its own mode of action and in fact, the mechanisms used by bacteria to attack termites remain elusive at the moment. Hence, the objective of this study was to evaluate the susceptibility of subterranean termites Coptotermes curvignathus to opportunistic pathogens using culturable aerobic bacteria isolated from the termite gut and its foraging pathways. Bacterial suspensions were prepared in concentrations of 10 3, 10 6 and 10 9 colony-forming units (CFU) ml −1 and introduced to the termites via oral-contact and physical contact treatment. The data show that contact method acted slower and gave lower mortality, compared to the oral-contact method. Coptotermes curvignathus were highly susceptible to Serratia marcescens and Pseudomonas aeruginosa . Serratia marcescens showed the highest mortality percentage of 68% and 54% at bacterial concentration of 10 9 CFU ml −1 via oral-contact and contact method, respectively. Serratia marcescens was also defined as the bacteria with the highest ability to induce the high mortality of C. curvignathus with the lowest concentration of bacterial suspension at a given time under laboratory condition. The results of this study indicate that P. aeruginosa and S. marcescens in particular may be attractive candidates worth further examination as a possible biocontrol agent against C. curvignathus in the field and to evaluate environmental and ecological risks of the biocontrol.